Inhomogeneous Dual Diophantine Approximation on Affine Subspaces. (11th June 2018) - Beresnevich, Victor; Ganguly, Arijit; Ghosh, Anish; Velani, Sanju
Abstract: We prove the convergence and divergence cases of an inhomogeneous Khintchine–Groshev-type theorem for dual approximation restricted to affine subspaces in R ^n . The divergence results are proved in the more general context of Hausdorff measures.